Clinical dissection of childhood occipital epilepsy of Gastaut and prognostic implication. (25th October 2015) - Verrotti, A.; Laino, D.; Rinaldi, V. E.; Suppiej, A.; Giordano, L.; Toldo, I.; Margari, L.; Parisi, P.; Rizzo, R.; Matricardi, S.; Cusmai, R.; Grosso, S.; et al.
Abstract : Background and purpose: Our aim was to describe the clinical and electrical features and the long‐term evolution of childhood occipital epilepsy of Gastaut (COE‐G) in a cohort of patients and to compare long‐term prognosis between patients with and without other epileptic syndromes. Methods: This was a retrospective analysis of the long‐term outcome of epilepsy in 129 patients with COE‐G who were referred to 23 Italian epilepsy centres and one in Austria between 1991 and 2004. Patients were evaluated clinically and with electroencephalograms for 10.1−23.0 years. The following clinical characteristics were evaluated: gender, patient age at seizure onset, history of febrile seizures and migraine, family history of epilepsy, duration and seizure manifestations, circadian distribution and frequency of seizures, history of medications including the number of drugs, therapeutic response and final outcome. Results: Visual hallucinations were the first symptom in 62% and the only manifestation in 38.8% of patients. Patients were subdivided into two groups: group A with isolated COE‐G; group B with other epileptic syndromes associated with COE‐G. The most significant ( P < 0.05) difference concerned antiepileptic therapy: in group A, 45 children responded to monotherapy; in group B only 15 children responded to monotherapy. At the end of follow‐up, the percentage of seizure‐free patients was significantly higher in group A than in group B. Conclusions: Childhood occipital epilepsy of Gastaut has an overall favourable prognosis and a good response to antiepileptic therapy with resolution of seizures and of electroencephalogram abnormalities. The association of typical COE‐G symptoms with other types of seizure could be related to a poor epilepsy outcome. Abstract : Clickhere for the corresponding questions to this CME article.